Mengembangkan Kemampuan Numerasi Dan Karakter Siswa Di SD Negeri Panggung 10 Dengan Barang Bekas - Muhammad Arif Budiman Sucipto; Handono Lakstianto; Lisa Nurul Huda; M. Hanif Tyas M; Muhamad Rizal Arfani; Noni Isniyadi; Puput Kurniawati; Ropiyah; Syaeful Amri Bagus Romadhon; Yuli Intan Sari (CV. Multi Kreasi Media, 2025)
Education at SD Negeri Panggung 10 faces significant challenges related to students' low numeracy skills, bullying, and gadget addiction. To address these issues, a leadership project was conducted aiming to improve students' numeracy skills through waste-based learning media and to solve social problems such as bullying and gadget addiction. Activities included the creation of a mathematical machine and abacus, numeracy games such as snakes and ladders and number relay races, as well as anti-bullying socialization through sociodrama and storytelling about gadget addiction using puppetry made from waste materials. The results of this activity showed an improvement in students' numeracy skills and their awareness of the dangers of bullying and excessive gadget use. By utilizing waste materials, students not only learned mathematics but also developed creativity and environmental awareness. Overall, this project successfully created a safer, more positive learning environment that supported the development of both character and numeracy skills in students.